The Effect of the Guided Inquiry Learning Model on Critical Thinking Skills in Science Education: A Systematic Literature Review - Luh Ririn Indahyani; I Wayan Redhana; I Nyoman Tika; Putu Artawan; I Nyoman Suardana (Thinking Skills and Creativity Journal, 2025)
Students’ critical thinking skills in science learning remain underdeveloped due to teacher-centered instructional practices that limit active engagement in inquiry and reasoning. This study aims to analyze empirical evidence on the effect of the guided inquiry learning model on students’ critical thinking skills. This research employed a systematic literature review (SLR) design involving 20 peer-reviewed scientific articles published in reputable journals. The selected articles were obtained through database searches using predefined inclusion and exclusion criteria. Data were collected using documentation techniques and analyzed through thematic content analysis focusing on learning characteristics, research design, instruments used, and reported outcomes. The results indicate that the guided inquiry learning model consistently demonstrates a positive and significant effect on improving students’ critical thinking skills, as reflected in their abilities to formulate problems, design investigations, analyze data, evaluate evidence, and draw conclusions. Moreover, guided inquiry promotes active learning, scientific reasoning, and student autonomy, although its implementation requires adequate teacher preparation and sufficient instructional time. In conclusion, guided inquiry is an effective and evidence-based instructional model for enhancing critical thinking skills in science education. These findings imply that educators and researchers are encouraged to integrate and further investigate guided inquiry to strengthen the quality of science learning and support the development of higher-order thinking skills.